The role of the “ligand periphery” in the coordination of tripodal triamidostannates(II) to iridium: simple ligation vs. cyclometallation : dedicated to Professor Heinrich Nöth on the occasion of his 80th birthday - Kilian, Michaela; Wadepohl, Hubert; Gade, Lutz H. (Zeitschrift für anorganische und allgemeine Chemie, 2008)
Reaction of the triamidostannates(II) MeSiSiMe2N(3,5-xyl)3SnLi(OEt2) (2a) and MeSiSiMe2N(p-tol)3SnLi(OEt2) (2b) with [IrCl(CO)(PPh3)2] gave the IrI-Sn complex [MeSiSiMe2N(3,5-xyl)3SnIr(PPh3)2(CO)] (3a) for the former. In contrast, for the tolyl stannate CH-activation occurred to give the IrIII compound [MeSiSiMe2N(p-tol)2SiMe2N(2-C6H3-4-CH3)SnIr(H)(PPh3)2(CO)] (3b). The latter is thus avoided by introduction of suitably placed substituents in the peripheral aryl groups of the triamidostannate ligand.
First published: 26 May 2008
Gesehen am 08.12.2022
Keywords: Festschrift